Watermelon-Induced Hyperkalemia: A Case Series - Sushmita Prabhu; Arunava Saha; Suzanne Martin (Annals of Internal Medicine: Clinical Cases)
Hyperkalemia is a potentially life-threatening electrolyte disorder. In patients with stable chronic kidney disease, on stable doses of renin–angiotensin–aldosterone system inhibitors and with adequate distal sodium delivery, an exogenous source of increased potassium intake should be investigated in patients with new hyperkalemia. Watermelon is an under-recognized source of excess dietary potassium, with 2 wedges (1/8th of a watermelon) containing 16.4 mmol (640 mg) of potassium. This emphasizes the importance of dietary counseling in patients with advanced chronic kidney disease, including end-stage renal disease. We present a case series of 3 patients with excess watermelon consumption causing severe hyperkalemia.